COVID-19: Policy Evaluation to Protect Communities Through Social Safety Net - Nahot Tua Parlindungan Sihaloho; Marto Silalahi; Bima Sujendra (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political Social UMA), 2020)
Various forms of restrictions due to the outbreak of Covid-19 in North Sumatra increasingly led to non-medical impacts, namely the weakening of the people's economy. This condition was then addressed by the Social Safety Net (SSN) program. Using secondary data in official government reports, research results, and mass media, this qualitative research seeks to evaluate the implementation of the program. The data collected was analyzed following the steps put forward by Miles et al. (2014). The results showed that the distribution of JPS has not been able to fully guarantee the economic protection and safety of the community. Although JPS reduces the risk of economic slowdown, JPS has not been able to mitigate the conflicts that have so far occurred in North Sumatra. The implications of this study confirm three things. First, the implementation of JPS has not been successful as a whole because of the characteristics of the community who are not ready for the prerequisites to undergo new normal. Second, the obstacles that arise are social conflicts, both vertically and horizontally. Third, the need for careful preparation in the first two stages in the standard implementation of public policies, namely the preparation of the agenda and drafting and consulting. However, public policy cannot be one size fits all. Therefore, decision making needs to be based on the social characteristics of each region.